Factors Influencing In Vitro Killing of Bacteria by Hemocytes of the Eastern Oyster (Crassostrea virginica) - Genthner, Fred J. (American Society for Microbiology, 1999)
A tetrazolium dye reduction assay was used to study factors governing the killing of bacteria by oyster hemocytes. In vitro tests were performed on bacterial strains by using hemocytes from oysters collected from the same location in winter and summer. Vibrio parahaemolyticus strains, altered in motility or colonial morphology (opaque and translucent), and Listeria monocytogenes mutants lacking catalase, superoxide dismutase, hemolysin, and phospholipase activities were examined in winter and summer. Vibrio vulnificus strains, opaque and translucent (with and without capsules), were examined only in summer. Among V. parahaemolyticus and L. monocytogenes, significantly (P < 0.05) higher levels of killing by hemocytes were observed in summer than in winter. L. monocytogenes was more resistant than V. parahaemolyticus or V. vulnificus to the bactericidal activity of hemocytes. In winter, both translucent strains of V. parahaemolyticus showed significantly (P < 0.05) higher susceptibility to killing by hemocytes than did the wild-type opaque strain. In summer, only one of the V. parahaemolyticus translucent strains showed significantly (P < 0.05) higher susceptibility to killing by hemocytes than did the wild-type opaque strain. No significant differences (P > 0.05) in killing by hemocytes were observed between opaque (encapsulated) and translucent (nonencapsulated) pairs of V. vulnificus. Activities of 19 hydrolytic enzymes were measured in oyster hemolymph collected in winter and summer. Only one enzyme, esterase (C4), showed a seasonal difference in activity (higher in winter than in summer). These results suggest that differences existed between bacterial genera in their ability to evade killing by oyster hemocytes, that a trait(s) associated with the opaque phenotype may have enabled V. parahaemolyticus to evade killing by the oyster’s cellular defense, and that bactericidal activity of hemocytes was greater in summer than in winter.